Infections in hematologic malignancy patients treated by CD19 chimeric antigen receptor T‐cell therapy - Linghui Zhou; Elaine Tan Su Yin; Houli Zhao; Shuyi Ding; Yongxian Hu; He Huang (ImmunoMedicine, 2022)
Abstract Increasing use of chimeric antigen receptor‐T (CAR‐T) cell therapy has significantly improved the survival of hematologic malignancy patients, but CAR‐T cell treatment is also associated with increased risk of infection. Hence, understanding the characteristics of infection may improve disease prognosis. The data of post‐CAR‐T therapy infections were obtained from the VigiBase database. We identified a total of 554 infection reports (1001 infection events) involving CAR‐T therapy among the 3007 case reports. Infections occurred in 18.42% of cases reported in VigiBase with CAR‐T therapy and were most frequently occurred during the first month. Among cases reported in VigiBase, most of the infections were controllable, and only 4.4% of the cases were fatal. Bacteria (60.7%) and respiratory tract infection (50.9%) were the most common infection types. Compared with axicabtagene ciloleucel, infection in patients receiving tisagenlecleucel‐T therapy had a higher infection risk (ROR = 1.76; 95% CI = 1.46–2.12, p < 0.001). Meanwhile, fungus infection and mixed infection had poorer prognoses than virus infection. Concerning the disease prognoses, fungal and mixed infection should be given more attention, and extensive prospective studies are much needed to verify these findings.